The Determination of Bedrock Depth Using Seismic Refraction Method in Kemuning Lor Village, Sub District of Arjasa, Jember - Nurul Priyantari; Agus Supriyanto (Jurnal ILMU DASAR, 2009)
A research has been done using seismic refraction method to determine the depth of bedrock in the Village of Kemuning Lor, sub district of Arjasa, Jember. The Data acquisition was done by using 12 geophones and using weight drop vibrations sources. The distance between the vibration source and the first geophone is 10 meters away, while the distance among geophones is 2 meter away each. This Data acquisitions used two tracks (the first track was about 90 meters and the second track was about 40 meters). The first and second track were crossing each other, the first track lied from the main road to crevasse, while the second track lied in line with the crevasse. The result was that we were able to obtain three layers having the depth of 3,03-6,76 m; 4,37-9,93 m and 10,68-13,32 m, and having spreading speed 168,9-198,8 m; 425,1-511,7 m and 909,1-972,2 m. The obtained bedrock profile had declivity toward the crevasse and is assumed to have the potential of soil movement.